2022
DOI: 10.3390/molecules27175590
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile, Antioxidant and Enzyme Inhibitory Activities of Leaves from Two Cassia and Two Senna Species

Abstract: Several species within the genera Cassia or Senna have a treasure of traditional medicines worldwide and can be a promising source of bioactive molecules. The objective of the present study was to evaluate the phenolic content and antioxidant and enzyme inhibition activities of leaf methanolic extracts of C. fistula L., C. grandis L., S. alexandrina Mill., and S. italica Mill. The two Cassia spp. contained higher total polyphenolic content (42.23–49.75 mg GAE/g) than the two Senna spp., and C. fistula had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The details of the homology modeling are available in the Ref. [ 56 ]. All protein structures were prepared according to the protocol described in the Ref.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the homology modeling are available in the Ref. [ 56 ]. All protein structures were prepared according to the protocol described in the Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Means with letters a; b; c in the same row are diferent (p < 0.05); Means with * ; * * ; * * * in the same column are diferent for D0 and D14 of the same parameter. * � p < 0.05; * * � p < 0.01; * * * � p < 0.001. attributed to them[23]. Te study showed that the aqueous extract (p < 0.001) has the highest proportion of total phenol (1497.24% ± 21.55) and of favonoids (1278.11% ± 21.23) (p < 0.0001).…”
mentioning
confidence: 92%
“…However, the crystal structures of human tyrosinase and glucosidase are not available; therefore, Priestia megaterium tyrosinase (PDB ID: 6QXD) [ 82 ] and Mus musculus alpha-glucosidase (PDB ID: 7KBJ) [ 83 ] were retrieved and used as templates to build their human models using the respective human sequences and UniProt entries P14679 and P0DUB6. The detailed procedure of the model building was described previously in [ 84 ]. The pKa of titratable residues in each protein was predicted using the “Playmolecule ProteinPrepare” module [ 85 ] and was then used to prepare the proteins at a physiological pH of 7.4.…”
Section: Methodsmentioning
confidence: 99%